Ocular albinism with infertility and late‐onset sensorineural hearing loss. Issue 7 (16th July 2018) - Fabian‐Jessing, Bjørn K.; Vestergaard, Else Marie; Plomp, Astrid S.; Bergen, Arthur A.; Dreschler, Wouter A.; Duno, Morten; Winiarska, Beata S.; Neumann, Linda; Gaihede, Michael; Vorum, Henrik; Petersen, Michael B.
Abstract : Ocular albinism type 1 (OA1) is caused by mutations in the GPR143 gene located at Xp22.2. The manifestations, which are due to hypopigmentation, are confined to the eyes and optic pathway. OA1 associated with late‐onset sensorineural hearing loss was previously reported in a single family and hypothesized to be caused by a contiguous gene deletion syndrome involving GPR143 and the adjacent gene, TBL1X . Here, we report on a family with OA1, infertility, late‐onset sensorineural hearing loss, and a small interstitial Xp microdeletion including the GPR143, TBL1X, and SHROOM2 genes. In addition, we re‐examined a patient previously described with OA1, infertility and a similar Xp deletion with audiologic follow‐up showing a late‐onset sensorineural hearing loss. Our results raise an intriguing question about the possibility for TBL1X (absence) involvement in this type of hearing loss. However, our study cannot claim a causative relationship and more convincing evidence is needed before the hypothesis can be accepted that TBL1X could be involved in late‐onset sensorineural hearing loss and that ocular albinism with late‐onset sensorineural hearing loss can present itself as a contiguous gene deletion/microdeletion syndrome. The finding of infertility in all affected male patients demonstrates that this deletion, including the SHROOM2 gene, may be a potentially causative X‐linked genetic factor of male infertility.